Granulosa cells express three inositol 1,4,5-trisphosphate receptor isoforms: cytoplasmic and nuclear Ca2+ mobilization - Morales-Tlalpan Verónica; Arellano Rogelio O; Juárez-Espinosa Anna; de la Rosa Santander Patricia; Díaz-Muñoz Mauricio (BMC, 2008)
Abstract Background Granulosa cells play an important endocrine role in folliculogenesis. They mobilize Ca2+ from intracellular stores by a coordinated action between 1,4,5 inositol trisphosphate and ryanodine receptors (IP3R and RyR). The aim of this study was to explore the isoforms of IP3Rs expressed in mouse C57BL/6 NHsd granulosa cells, characterizing their intranuclear localization and the relation with other Ca2+-handling proteins. Methods Ovarian tissue and granulosa cells were analyzed by multiphotonic and confocal microscopy to determine the intracellular presence of IP3R types 1, 2 and 3, RyR, thapsigargin-sensitive Ca2+-ATPase, and endomembranes. Cellular fractionation and Western blot assays were also used to further confirm the nuclear occurrence of the three IP3R isoforms. Free nuclear and cytosolic Ca2+ concentrations were measured using Fluo-4 AM by confocal microscopy. Results By using antibodies and specific fluorophores, was shown that granulosa cells endomembranes contain three isoforms of IP3R, the RyR, and the thapsigargin-sensitive Ca2+-ATPase (SERCA). Interestingly, all these proteins were also detected in the nuclear envelope and in well-defined intranuclear structures. Microsomal membranes depicted characteristic bands of the 3 types of IP3R, but also variants of lower molecular weight. Analysis of nuclear membranes and nucleoplasmic fraction confirmed the nuclear localization of the IP3R types 1, 2 and 3. We demonstrated ATP-induced Ca2+ transients in the nuclear and cytoplasmic compartments. Remarkably, the inhibitory effect on ATP-induced Ca2+ mobilization of brefeldin A was more accentuated in the cytoplasm than in the nucleus. Conclusion These findings provide evidence that granulosa cells, including nuclei, express the Ca2+-handling proteins that allow Ca2+ mobilization. All three IP3R were also detected in ovarian slices, including the nuclei of granulosa cells, suggesting that these cells use the three IP3R in situ to achieve their physiological responses.